Strategi Peningkatan Minat Pelanggan Pendidikan di Madrasah - Mukhamad Sukur; Mohammad Ja'far As-Shodiq (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The existence of a madrasa is in principle very much determined by the level of interest of the community who are interested in getting the services it offers. Madrasahs must have the readiness to be the best and superior in order to win the hearts of the educational community in the midst of competition between educational institutions which is increasingly complex because the parameters for selecting schools for modern society are no longer based on the status of public or private schools but on quality and popularity, both in terms of school capabilities. in introducing science and technology as well as the ability to shape the spiritual morals (religiosity) of students. In this case, one of the keys is the ability of madrasah managers to develop marketing strategies. The research results obtained; 1) The strategy for determining the products of Islamic educational institutions is carried out by reducing the vision, mission and goals of madrasas in the form of educational products (programs) that are rational in accordance with the human resources and infrastructure they have and are competitive in competing for achievements between institutions and gaining the attention and interest of customers; 2) The cost determination strategy is carried out by rationalizing the amount of costs based on the quality of the education program, general regional education costs, affordability, and the financing system which is carried out through a joint agreement mechanism with the madrasah committee and student parents; 3) The institution's promotion strategy uses a systems approach involving all components of the madrasa, involving parents and students as madrasa agents, in the publication and socialization of the vision, mission, goals, programs, achievements and acceptance of new students via the internet and print media.